Characterizing two solar-type Kepler subgiants with asteroseismology: KIC 10920273 and KIC 11395018 - Doğan, Gulnur; Metcalfe, T. S.; Deheuvels, S.; Mauro, M. P. Di; Eggenberger, P.; Creevey, O. L.; Monteiro, M. J. P. F. G.; Pinsonneault, M.; Frasca, A.; Karoff, C.; Mathur, S.; Sousa, S. G.; et al. (The astrophysical journal, 2013)
Determining fundamental properties of stars through stellar modeling has improved substantially due to recent advances in asteroseismology. Thanks to the unprecedented data quality obtained by space missions, particularly CoRoT and Kepler, invaluable information is extracted from the high-precision stellar oscillation frequencies, which provide very strong constraints on possible stellar models for a given set of classical observations. In this work, we have characterized two relatively faint stars, KIC 10920273 and KIC 11395018, using oscillation data from Kepler photometry and atmospheric constraints from ground-based spectroscopy. Both stars have very similar atmospheric properties; however, using the individual frequencies extracted from the Kepler data, we have determined quite distinct global properties, with increased precision compared to that of earlier results. We found that both stars have left the main sequence and characterized them as follows: KIC 10920273 is a one-solar-mass star (M = 1.00 ± 0.04 M ☉), but much older than our Sun (t = 7.12 ± 0.47 Gyr), while KIC 11395018 is significantly more massive than the Sun (M = 1.27 ± 0.04 M ☉) with an age close to that of the Sun (t = 4.57 ± 0.23 Gyr). We confirm that the high lithium abundance reported for these stars should not be considered to represent young ages, as we precisely determined them to be evolved subgiants. We discuss the use of surface lithium abundance, rotation, and activity relations as potential age diagnostics.
Gesehen am 17.12.2020